Bending capacity of reinforced concrete beam with a rough aggregate of 2/3 teak pieces - Purwanto Purwanto; Iman Satyarno; Andreas Triwiyono (International Conference on Coastal and Delta Areas, 2017)
The development of science, especially in civil engineering, demands a better concrete technology. Replacing the rough aggregate with teak pieces of length 2 cm, width 3 cm, and height 2 cm was tried to reduce the weight of the concrete. This wood was selected because of its light. The testing phases included: testing of concrete cylinders and testing of reinforced concrete beam bending. The bending beam test was done by making a specimen with dimension of beam: width 120 mm, height 150 mm, and length 1200 mm. The main reinforcements used were 2Ø10 mm and 3Ø10. For the chock, Ø6-50 reinforcement bar was used. On the test of concrete cylinder results with soaked rough aggregates, it was found that compressive strength at 28 days old was 5.09 MPa and 4.74 MPa for non-soaked aggregate. On the test of reinforced concrete beams with 2 pieces of tensile reinforcement, it was found the average maximum load of 26300 N and average deflection of 6.99 mm. The average of reinforced concrete beam with 3 pieces of tensile reinforcement was 30500 N and average deflection of 8.66 mm. The bending strength of reinforced beam with 3 pieces of tensile reinforcement average was 5.34.106 Nmm. The comparison of calculation result between experiment and theory was found that load and moment for 2 pieces of tensile reinforcement was 0,72%, while comparison between load and moment for 3 pieces of tensile reinforcement was 0,58%. Keywords: teak wood, lightweight concrete, load beam capacity.